Synthesis and magnetic properties of heteronuclear 3d-4f compound - Cristóvão, Beata; Ferenc, Wieslawa (Eclética Química, 2007)
A novel heteronuclear 3d-4f compound having formula NdCu 3 L 3 ·13H 2 O (where H 3 L = Schiff base derived from 5-bromosalicylaldehyde and glycylglycine and L 3– = C 11 H 8 N 2 O 4 Br) was obtained. It was characterized by elemental and thermal analyses and magnetic measurements. The Cu(II)–Nd(III) compound is stable up to 323 K. During dehydration process the water molecules are lost in two stages. The magnetic susceptibility data for this complex change with temperature according to the Curie-Weiss law with Θ = -35 K. The magnetic moment values decrease from 5.00 μ B at 303 K to 4.38 μ B at 76 K.